Risk factors for postpartum depression in mothers of newborns admitted to neonatal intensive care unit - Lasheras, Gracia; Farré-Sender, Borja; Porta, Roser; Mestre-Bach, Gemma (Routledge, 2022)
Background: There is a lack of information on how maternal stress coping styles during admission of the newborn to the neonatal intensive care unit (NICU) influences the onset of the postpartum depression (PPD). We examined potential risk factors for the emergence of the PPD in mothers whose infants were admitted to the NICU. Methods: A cross-sectional study was conducted on 401 mothers, 125 were mothers whose infants were admitted to the NICU and 276 mothers without NICU care. Newborn illness severity information score was taken throughout NICU admission via the Clinical Risk Index for Babies (CRIB). Six weeks after giving birth, participants from both groups individually completed the Edinburg Postnatal Depression Scale (EPDS), the Postpartum Bonding Questionnaire (PBQ) and the Coping Strategies Inventory (CSI) using an online platform. Results: No differences were found regarding PPD and bonding in either groups. Multivariate analysis provided a final model in which cognitive restructuring, problem avoidance, severity of neonatal health problems during the first 12 hours of life, and problem solving were the best predictors of postpartum depression explaining, 43.7% of the variance in the NICU group. Conclusion: It is necessary to obtain early detailed information on coping styles in the NICU environment to prevent the possible onset of PPD. © 2020 Society for Reproductive and Infant Psychology.
Keywords: mother/s; neonatal intensive care; postnatal care; postnatal depression; quantitative methods; Scopus; JCR